A participação do cinema na dinamização de imaginários sobre o transtorno do espectro autista - Ethur, Marília Scheeren (2020)
This work has as general objective to understand the participation of the cinema in the dynamization of the imaginary about the autistic spectrum disorder (ASD) in the childhood. Imaginary in the cinema are readings, rereadings, meaning, resignification, interpretation, it is an unreal real. The imaginary generates bonds, relationships, beliefs. Cinema is a powerful generator of imaginary, which initiates individual and can become collective, but each viewer crystallizes the imaginary from their worldview. There was a selection of six films produced between 2004 and 2017 that deal with autism spectrum disorder in childhood. The selected films were: Farol das Orcas (2016), Um Elo de Amor (2015), Fly Away (2011), Um Amigo Inesperado (2006), Uma Família Especial (2005) and Missão Especial (2004). The research problem of this work is: from what characteristics do these films dynamize imaginaries? What would be the cristallized imaginary? The methodology used was character analysis, where an adapted character profile table was made, based on Campos’ (2011) character profile table, and in addition, certain dialogues of the characters from the films were inserted in the work, for a better understanding of their universe. The main results were the identification of elements of ASD corresponding to the following manifestations in children: ingenuity; purity; intelligence; photographic memory; attachment to routine; difficulty of communication; mothers of children without social life, abandoned by their partner most of the time; lack of specialized education; prejudice and prejudgment by acquaintances or strangers; attachment to the mother; love of animals; sensitivity. We can understand that they are drawn from these elements, imaginary of sensitivity, difference and even exclusion and inclusion